Strategi Komunikasi Pemasaran Trialista Beauty Dalam Meningkatkan Penjualan - Rista Dwi Lestari; Saifuddin Zuhri (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Trialista Beauty is one of the local brands that has milk soap products that have succeeded in growing rapidly, especially in the online market. The purpose of this research is to find out what marketing strategy is being carried out by Trialista Beauty to further increase sales every month. This research is a type of descriptive research using a qualitative approach as well as a qualitative descriptive method. Then, the data collection techniques in this study used three techniques, namely observation, in-depth interviews, and documentation. Trialista Beauty is a beauty brand that has milk soap products. In marketing, Trialista beauty uses two channels, namely online and offline. The results of this study indicate that Trialista Beauty uses several elements of the promotional mix to market milk soap products. Some of these elements are advertising (advertising, sales promotion), personal selling (personal selling), and interactive marketing (interactive marketing). advertising) and sales promotion using the Facebook application, then offline using personal selling and interactive marketing. Facebook also has an influence on increasing purchases. Keywords: Marketing strategy, milk soap product, promotion mix.